Pendidikan Masyarakat Adat dalam Kerangka Kurikulum Indonesia - Varary Mechwafanitiara Cantika; Asep Herry Hernawan; Laksmi Dewi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to analyze the implementation of indigenous community-based education in the Indonesian national curriculum, especially the Merdeka Curriculum, with a focus on meeting cultural needs and local wisdom. In the context of Indonesia's ethnic diversity, indigenous community education faces significant challenges, such as limited access, curriculum relevance, and lack of recognition of local wisdom. In order to uncover the potential and strategies for incorporating culture-based education into the national curriculum, this study employs a qualitative approach and a literature review method, specifically examining scientific literature and Indonesian government regulations on education for indigenous communities. We carried out the data analysis using an interactive model. The results of the study indicate that indigenous communities need education that takes into account their cultural context, especially to develop high-level thinking skills and understand the global world without losing cultural identity. These findings also emphasize the importance of the classroom as an inclusive intercultural environment. In addition, this study highlights the importance of integrating indigenous content into the Merdeka Curriculum through the Pancasila Student Profile Strengthening Project (P5), which is relevant to Goal 4 of the Sustainable Development Goals (SDGs) for inclusive education. This study recommends involving indigenous communities in curriculum design, training teachers to understand local contexts, and developing policies that support culture-based education. Future research should also explore the impact of local wisdom-based education on the quality of life of indigenous peoples, as well as conducting comparative studies with similar policies in other countries.